Índices de estado trófico, eutrofização e dominância de cianobactérias em açude do Semiárido cearense durante forte defict hídrico - Lima, Paulo de Freitas (2016)
The reservoirs in the Brazilian semiarid region are influenced by climatic factors and hydrological conditions that make these vulnerable ecosystems to eutrophication and dominance and persistence of cyanobacteria. In prolonged drought, with strong water deficit, reducing water quality, assessed by the trophic conditions and biological attributes of phytoplankton assemblages, it is more intense and cause ecological, social and economic damage to the region, which historically has problems water availability. The analysis of climatic and hydrological factors on the trophic conditions and the composition and structure of phytoplankton assemblages was based on limnological data collected in the Pereira de Miranda reservoir, semiarid region of the State of Ceará, in the beginning of the second prolonged drought cycle recorded the twenty-first century, which began with the drought of 2011 and still remains in 2016. However, this study was restricted to the time period of January 2012 to December 2013, characterized as dry season due to low rainfall, a sharp reduction the water level and gradual increase in the theoretical hydraulic residence time and higher wind speed, more intense in the second half of each year. In Chapter 2, we performed the estimation of trophic conditions of the Pereira de Miranda reservoir, established from the trophic state index, when there was estimated ranging from eutrophic and hypertrophic, based on the total phosphorus concentrations, and mesotrophic from the concentrations chlorophyll a, although it has been found strong evidence that the total phosphorus was the main limiting nutrient or co-limiting with total nitrogen. The observation of these differences was important to highlight the sensitivity of the results of trophic state indices adopted the influence of environmental factors such as the effects of the reduction in the optical quality of the water on lower primary production algal. Based on this evidence, the applicability of the indices of trophic states, prepared for climate regions Temperate, Tropical and Subtropical was evaluated in Chapter 3, based on the Pereira de Miranda reservoir data. The results of the original index Carlson and adapted indices for region Subtropical/Tropical Brazil were different, with distinct trophic ratings, although it has been observed general trend toward increasing the degree of eutrophication (eutrophic to hypertrophic) of the Pereira Miranda reservoir, associated with the increase in total phosphorus concentrations and reduce the transparency of the water, to the extent of dry interanual, especially in the shallower points. A small seasonal variation of low concentrations of chlorophyll a resulted in maintaining the mesotrophic state. The gradual reduction of water transparency with the drought, the increase of mineral turbidity was indicative of the potential limitation of primary production by the low availability of underwater light, since the availability of nutrients, mainly in the dry period and in the shallower points, it was sufficient to cause increased algal biomass. So as to maintain low concentrations of chlorophyll a, despite favorable nutritional conditions, it may be a common condition in shallow reservoirs in the semi-arid region of Brazil, where the complete mixing of water masses favors the reduction of underwater radiation, the validity the results of trophic state index for Semi-arid regions may be questioned. On the other hand, differences between the results of the indices as observed from of the chlorophyll a concentrations of total phosphorous can be essential for identifying which environmental variables can influence these differences, such as the physical dynamics of aquatic ecosystems caused by temperature air, wind and rain. In Chapter 4, the phytoplankton assemblies were evaluated based on trophic and hydrological conditions of the Pereira de Miranda reservoir, established by climatic particularities of the semiarid region. During the search, due to the strong water deficit, continuous reduction in water level, strong wind action, predominantly mixtures of conditions of water bodies, few events thermal micro stratifications, maintenance alkaline conditions, reducing the transparency of the water, increase in turbid and trophic conditions of water and low concentrations of chlorophyll a, phytoplankton assemblies Miranda Pereira reservoir were characterized by low richness in species and greater abundance, dominance and persistence of cyanobacteria. The phytoplankton assemblages showed temporal pattern, characterized by sequential switching of the most abundant species (Planktothrix agardhii, Cylindrospermopsis raciborskii and Microcystis sp.), with prolonged drought. The Planktothrix agardhii was dominant in 2012, associated with greater depth and better optical quality of the water. The species Cylindrospermopsis raciborskii showed higher relative abundance from October 2012 to February 2013, associated with the reduction in total nitrogen availability. In the same period, the Microcystis sp. (Unit) increased its abundance and became the dominant species of February 2013 until the end of the survey. In Pereira de Miranda reservoir, dominance and persistence of potentially toxic cyanobacteria and forming blooms can be explained by the establishment of lasting unstable conditions due to prolonged drought, when other factors and nutrients, such as reducing underwater radiation associated the gradual reduction in water transparency were important to explain temporal changes on the composition and structure of phytoplankton assemblages.